Space-time contours to treat intense field-dressed molecular states - Paul, Amit K.; Adhikari, Satrajit; Baer, Michael (The Journal of chemical physics, 2010)
In this article we consider a molecular system exposed to an intense short-pulsed external field. It is a continuation of a previous publication [ A. K. Paul , S. Adhikari , D. Mukhopadhyay , J. Phys. Chem. A 113 , 7331 ( 2009 ) ] in which a theory is presented that treats quantum effects due to nonclassical photon states (known also as Fock states). Since these states became recently a subject of intense experimental efforts we thought that they can be treated properly within the existing quantum formulation of dynamical processes. This was achieved by incorporating them in the Born-Oppenheimer (BO) treatment with time-dependent coefficients. The extension of the BO treatment to include the Fock states results in a formidable enhancement in numerical efforts expressed, in particular, in a significant increase in CPU time. In the present article we discuss an approach that yields an efficient and reliable approximation with only negligible losses in accuracy. The approximation is tested in detail for the dissociation process of H 2 + as caused by a laser field.